2010
DOI: 10.1073/pnas.1000866107
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear entry of a cGMP-dependent kinase converts transient into long-lasting olfactory adaptation

Abstract: To navigate a complex and changing environment, an animal's sensory neurons must continually adapt to persistent cues while remaining responsive to novel stimuli. Long-term exposure to an inherently attractive odor causes Caenorhabditis elegans to ignore that odor, a process termed odor adaptation. Odor adaptation is likely to begin within the sensory neuron, because it requires factors that act within these cells at the time of odor exposure. The process by which an olfactory sensory neuron makes a decisive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 38 publications
1
95
0
Order By: Relevance
“…Experiments using a transgenic constitutively nuclear allele of egl-4 (NLS::GFP:: EGL-4) demonstrated that the nuclear accumulation of the protein was itself sufficient to phenocopy the conditioned response to Bnz (O'Halloran et al, 2009;Lee et al, 2010). The results thus far suggested that both the insulin signaling pathway and egl-4 function in the associative learning pathway.…”
Section: Insulin Signaling Is Only Required In Associative Learning Pmentioning
confidence: 72%
See 2 more Smart Citations
“…Experiments using a transgenic constitutively nuclear allele of egl-4 (NLS::GFP:: EGL-4) demonstrated that the nuclear accumulation of the protein was itself sufficient to phenocopy the conditioned response to Bnz (O'Halloran et al, 2009;Lee et al, 2010). The results thus far suggested that both the insulin signaling pathway and egl-4 function in the associative learning pathway.…”
Section: Insulin Signaling Is Only Required In Associative Learning Pmentioning
confidence: 72%
“…Our previous work (Lin et al, 2010) suggested the main function of insulin occurs during memory retrieval, and the work of Lee et al (2010) suggested that egl-4 functions in memory acquisition. Briefly, Lee et al (2010) demonstrated that the adaptation memory significantly outlasts the nuclear localization of EGL-4, and thus while its translocation may trigger formation of the engram, the physiological manifestation of memory, it is not the engram itself. Our result demonstrated that ins-1 is epistatic to egl-4 and is therefore consistent with the role of egl-4 in memory acquisition and insulin in memory retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By developing a molecular readout of olfactory plasticity that represents a nuclear translocation of a PKG in stimulated neurons, we provide a platform for rapid and detailed dissection of neuronal plasticity within an in vivo model. Using our molecular readout of olfactory adaptation we have begun to describe some of the events that shape olfactory adaptation in C. elegans 5,6,7 . However, this is just a beginning, and by studying this process as a function of age, sex, infection, or diet we may uncover important themes of neuronal plasticity at the circuit and systems level.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that cGKs are modulators of cell growth (Hofmann et al 2009). In Caenorhabditis elegans cGKs regulate growth processes, but also patterns of particular behavioral states (Raizen et al 2006, 2008, Fujiwara et al 2002, odor perception, and signal integration (Lee et al 2010). Finally, genome sequencing approaches have led to the identification of cGK orthologs also from protozoa.…”
Section: Introductionmentioning
confidence: 99%